Impact of COVID‐19, gender, race, specialty and seniority on mental health during surgical training: an international study. Issue 9 (18th August 2022) - Kovoor, Joshua G.; Layton, Georgia R.; Burke, Joshua R.; Churchill, James A.; Jacobsen, Jonathan Henry W.; Reid, Jessica L.; Edwards, Suzanne; Issa, Eyad; Garrod, Tamsin J.; Archer, Julian; Tivey, David R.; Babidge, Wendy J.; et al.
Abstract: Background: Superior patient outcomes rely on surgical training being optimized. Accordingly, we conducted an international, prospective, cross‐sectional study determining relative impacts of COVID‐19, gender, race, specialty and seniority on mental health of surgical trainees. Method: Trainees across Australia, New Zealand and UK enrolled in surgical training accredited by the Royal Australasian College of Surgeons or Royal College of Surgeons were included. Outcomes included the short version of the Perceived Stress Scale, Oxford Happiness Questionnaire short scale, Patient Health Questionnaire‐2 and the effect on individual stress levels of training experiences affected by COVID‐19. Predictors included trainee characteristics and local COVID‐19 prevalence. Multivariable linear regression analyses were conducted to assess association between outcomes and predictors. Results: Two hundred and five surgical trainees were included. Increased stress was associated with number of COVID‐19 patients treated ( P  = 0.0127), female gender ( P  = 0.0293), minority race ( P  = 0.0012), less seniority ( P  = 0.001), and greater COVID‐19 prevalence ( P  = 0.0122). Lower happiness was associated with training country ( P  = 0.0026), minority race ( P  = 0.0258) and more seniority ( P  < 0.0001). Greater depression was associated with more seniority ( P  < 0.0001). Greater COVID‐19 prevalence was associated with greater reported loss of training opportunities ( P  = 0.0038), poor working conditions ( P  = 0.0079), personal protective equipment availability ( P  = 0.0008), relocation to areas of little experience ( P  < 0.0001), difficulties with career progression ( P  = 0.0172), loss of supervision ( P  = 0.0211), difficulties with pay ( P  = 0.0034), and difficulties with leave ( P  = 0.0002). Conclusion: This is the first study to specifically describe the relative impacts of COVID‐19 community prevalence, gender, race, surgical specialty and level of seniority on stress, happiness and depression of surgical trainees on an international scale. Abstract : This is the first study to specifically describe the relative impacts of COVID‐19 community prevalence, gender, race, surgical specialty and level of seniority on stress, happiness and depression of residents undergoing surgical training on an international scale.